Access to, interest in and attitude toward e-learning for continuous education among Malaysian nurses. (January 2016) - Chong, Mei Chan; Francis, Karen; Cooper, Simon; Abdullah, Khatijah Lim; Hmwe, Nant Thin Thin; Sohod, Salina
Summary: Background: Continuous nursing education (CNE) courses delivered through e-learning is believed to be an effective mode of learning for nurses. Implementation of e-learning modules requires pre-assessment of infrastructure and learners' characteristics. Understanding the learners' needs and their perspectives would facilitate effective e-learning delivery by addressing the underlying issues and providing necessary support to learners. Objective: The aim of this study was to examine access to computer and Internet facilities, interest in and preferences regarding e-learning, and attitudes toward e-learning among nurses in Peninsular Malaysia. Design: The study utilized a cross-sectional descriptive survey. Setting: Government hospitals and community clinics in four main regions of Peninsular Malaysia. Participants: A total of 300 registered nurses. Method: Data were collected using questionnaires, which consisted of demographic and background items and questions on access to computer and Internet facilities, interest and preferences in e-learning, and attitudes toward e-learning. Descriptive analysis and a chi-squared test were used to identify associations between variables. Results: Most Malaysian nurses had access to a personal or home computer (85.3%, n = 256) and computer access at work (85.3%, n = 256). The majority had Internet access at home (84%, n = 252) and at work (71.8%, n = 215); however, average hours of weekly computer use were low. Most nurses (83%, n = 249) did not have an e-learning experience but were interested in e-learning activities. Most nurses displayed positive attitudes toward e-learning. Average weekly computer use and interest in e-learning were positively associated with attitudes toward e-learning. Conclusion: Study findings suggest that organizational support is needed to promote accessibility of information and communications technology (ICT) facilities for Malaysian nurses to motivate their involvement in e-learning. Highlights: The majority of nurses have access to computer and Internet at home and at the workplace. Average hours of weekly computer use among Malaysian nurses are relatively low. Nurses have more interest and positive attitudes toward synchronous e-learning. Computer usage and interest in e-learning influence the attitude toward e-learning.